2008
DOI: 10.1063/1.2827868
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of length dependence of conductance in alkanedithiols

Abstract: Electronic transport properties of alkanedithiols are calculated by a first-principles method based on density functional theory and nonequilibrium Green's function formalism. At small bias, the I-V characteristics are linear and the resistances conform to the Magoga's exponential law. The calculated length-dependent decay constant gamma which reflects the effect of internal molecular structure is in accordance with most experiments quantitatively. Also, the calculated effective contact resistance R(0) is in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 48 publications
2
33
1
Order By: Relevance
“…6, the current shows similar trend with the carbon number of chain for model B, as compared with model A at various biases. This behavior is not seen in some researches, 32,33 where a smooth decrease in conductance with length was observed. It is worth noting that the assuming cases to obtain our these results are very different from ones discussed in Ref.…”
Section: Fig 2 ͑A͒contrasting
confidence: 62%
“…6, the current shows similar trend with the carbon number of chain for model B, as compared with model A at various biases. This behavior is not seen in some researches, 32,33 where a smooth decrease in conductance with length was observed. It is worth noting that the assuming cases to obtain our these results are very different from ones discussed in Ref.…”
Section: Fig 2 ͑A͒contrasting
confidence: 62%
“…The phenylene molecular wires show a thermopower that grows linearly with length of the molecular backbone, while the alkanes show the opposite trend. Electrical transport through alkanedithiols connected between gold leads had previously been argued to be influenced by gateway states at the connection to the leads (Zeng et al, 2002;Zhou et al, 2008), but it was difficult to separate the contributions of in-gap states from those of HOMO or LUMO tunneling. By the additional information obtained through thermopower, Malen et al (2009) demonstrated the importance of gateway states.…”
Section: G Thermal and Thermoelectrical Propertiesmentioning
confidence: 99%
“…Gold was chosen as the current collector since thiol based SAMs on gold are extremely well characterized, their preparation straightforward, and several studies completed on the electron transport in thiol based molecular junctions5354555657. Furthermore, there is an extensive array of commercially available thiol terminated molecules with many different end groups.…”
Section: Resultsmentioning
confidence: 99%